Carbon quantum dots derived from the extracellular polymeric substance of anaerobic ammonium oxidation granular sludge for detection of trace Mn(vii) and Cr(vi). Issue 53 (1st September 2020) - Liu, Fengli; Li, Huosheng; Liao, Dandan; Xu, Yanhong; Yu, Mingxia; Deng, Shengwen; Zhang, Gaosheng; Xiao, Tangfu; Long, Jianyou; Zhang, Hongguo; Li, Yuting; Li, Keke; et al.
Abstract : Fluorescence detection of trace Mn(vii ) or Cr(vi ) by the CQDs prepared from anaerobic ammonium oxidation granular sludge. Abstract : Carbon quantum dots (CQDs) were synthesized via a hydrothermal method, in which extracellular polymeric substance (EPS) from anaerobic ammonium oxidation (anammox) granular sludge was used as a carbon precursor, while citric acid and ethylenediamine were applied as auxiliary carbon source and passivation agent, respectively. The synthesized CQDs, with orderly spherical shape and mean size of 7.15 nm, emitted blue fluorescent light under UV radiation of 365 nm. The CQDs had a high fluorescence yield (40.84%), with good water solubility and excellent spectroscopic properties. In addition, the CQDs exhibited selective, sensitive and distinctive fluorescence quenching behaviors for Cr(vi ) and Mn(vii ) in a PBS buffer solution (NaH2 PO4 –Na2 HPO4 ) of pH 7, with a detection limit of 5.8 nM for Cr(vi ) and 2.3 nM for Mn(vii ). Owing to the nitrogen components from the EPS of anammox granules, the CQDs were well nitrogen-doped, promoting electron-transfer and leading to reduction between the CQDs and Mn(vii )/Cr(vi ). These results indicate that CQD-based chemical sensing is a simple and efficient means for the fluorescence detection of Mn(vii ) and Cr(vi ).